Implementation of Active Learning Model with Integrated Digital Learning Media of Madura Local Culture - Siswoyo, Andika Adinanda (Universitas Trunojoyo Madura, 2023)
The low ability of students' cultural literacy in elementary schools is one of them influenced by the limitations of the teacher's ability to design active learning that integrates local culture. The low ability of students' cultural literacy in elementary schools is one of them influenced by the limitations of the teacher's ability to design active learning that integrates local culture. Rendahnya kemampuan literasi budaya siswa di sekolah dasar salah satunya dipengaruhi oleh keterbatasan kemampuan guru merancang pembelajaran aktif yang mengintegrasikan budaya lokal. The low ability of students' cultural literacy in elementary schools is influenced by the limited ability of teachers to design active learning that integrates local culture. Rendahnya kemampuan literasi budaya siswa di sekolah dasar dipengaruhi oleh keterbatasan kemampuan guru merancang pembelajaran aktif yang mengintegrasikan budaya lokal. Because it is necessary to implement an active learning learning model that is integrated through a digital learning media. This research is a type of descriptive research. The research subjects were grade 4 students at SDN Kamal 1 Bangkalan. Data collection techniques used are observation, tests, and questionnaires. Based on the results of the research, the implementation stages of the active learning learning model consist of planning, implementation, and evaluation stages through the application of an active learning model assisted by digital learning media integrated with the local culture of tanean lanjeng and roka' tase. The learning outcomes of student learning completeness reached 88% classically complete. Student responses during the learning process can be seen in the results of the student questionnaire showing a score of 85% with very interesting criteria. Student activity observation sheets are in the 80% category with active criteria. So it can be concluded that the application of active learning models assisted by digital learning media integrated with local culture is effective in learning in elementary schools.